Okült papiller tiroid kanseri metastazı: Lenfanjiyomu taklit eden kistik lateral boyun kitlesi - (:unkn) unknown (My University, 2015)
Bu yazıda metastatik kistik lateral boyun kitlesi ile başvuran 51 yaşında bir hasta sunuldu. Hastaya total tiroidektomi ve santral boyun kompartmanını da içeren tip 3 modifiye radikal boyun diseksiyonu uygulandı. Sağ tiroid lobundan kaynak- lanan mikrokarsinom odağı saptandı. Ameliyat sonrası erken dönemde sağ vokal kordda paralizi izlendi. Ameliyattan altı ay sonra vokal kord hareketleri düzeldi. Ameliyat sonrasında hastaya I-131 tedavisi uygulandı. Düzenli takiplerinde 24 ay boyunca nüks lehine bir bulgu saptanmadı. Okült papiller tiroid kanserinin sadece kistik boyun kitlesi olarak seyretmesi nadir görülen bir durumdur. Kistik boyun kitlelerinin ayırıcı tanısında okült papiller tiroid kanseri mutlaka göz önünde bulundurulmalıdır.

In this article, we report a 51-year-old patient who applied with metastatic cystic lateral neck mass. Patient was performed type 3 modified radical neck dissection including total thyroidec- tomy and central neck compartment. Microcarcinoma focus was detected generating from the right thyroid lobe. Paralysis was observed on the right vocal cord in the early postoperative period. Vocal cord movements improved at postoperative sixth month. Patient was administered I-131 treatment postopera- tively. Regular follow-up did not reveal any finding indicating relapse for 24 months. It is rare for occult papillary thyroid cancer to progress only as cystic neck mass. Occult papillary thyroid cancer should definitely be considered in the differen- tial diagnosis of cystic neck masses.
Occult pap illary thy roid carcinoma metastasis: p resenting as cystic lateral neck mass mimicking ly mphangioma
Keywords: Kulak, Burun, Boğaz